2021
DOI: 10.3389/fonc.2021.603223
|View full text |Cite
|
Sign up to set email alerts
|

BAP1-Altered Malignant Pleural Mesothelioma: Outcomes With Chemotherapy, Immune Check-Point Inhibitors and Poly(ADP-Ribose) Polymerase Inhibitors

Abstract: ObjectivesLittle is known regarding the outcomes of systemic treatments in BAP1-altered malignant pleural mesothelioma (MPM).Materials and MethodsForty five patients with MPM [group A: eight MPM patients with BAP1 inactivating mutation/copy number loss (FoundationOne® CDx/TEMPUSxT), selected from the electronic databases of four Israeli cancer centers (ICC); group B: 37 consecutive (years 2016–2018) MPM patients selected from the electronic databases of two ICC—of those six patients without a BAP1 alteration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…[20][21][22][23][24] Few studies have specifically evaluated the association of BAP1 IHC status with platinum and pemetrexed treatment. 14,25,26 On the basis of the biological function of BAP1 and longer survival in treated patients with BAP1 germline mutation, we postulated that loss of BAP1 in the tumor may predict survival after platinum and pemetrexed treatment in a general PM cohort.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] Few studies have specifically evaluated the association of BAP1 IHC status with platinum and pemetrexed treatment. 14,25,26 On the basis of the biological function of BAP1 and longer survival in treated patients with BAP1 germline mutation, we postulated that loss of BAP1 in the tumor may predict survival after platinum and pemetrexed treatment in a general PM cohort.…”
Section: Introductionmentioning
confidence: 99%
“…CDKN2A loss has been correlated with worst outcome 12 or proposed as a diagnostic tool, as observed in more than 75% of mesothelioma 13 . BAP1 is also frequently altered in mesothelioma, however a recent study highlights no difference in response to treatment (chemotherapy, immune checkpoint inhibitors or PARP inhibitors) between BAP1 wild-type or mutant mesothelioma 14 . For thymic malignancies, we were unable to confirm findings from TCGA as GTF2I was not part of any of the panels used in SPECTAlung and the sample size was very small.…”
Section: Discussionmentioning
confidence: 96%
“…The Food and Drug Administration (FDA) recently approved a combination of ipilimumab and nivolumab as the primary treatment option for MPM that cannot be treated by surgical intervention [ 78 ]. The clinical outcome of BAP1 mutation in MPM patients treated with immunotherapy was studied by Dudnik et al The study found that treatment response to PD-1/PD-L1 inhibitors was not defined by the presence of BAP1 mutations [ 79 ]. However, a combination of BAP1 mutations, mucin proteins, and immunoregulatory factors may be of value.…”
Section: The Connection Between Epi-mirna and Breast Cancer Gene 1-as...mentioning
confidence: 99%